Perancangan Komik Edukasi Borderline Personality Disorder untuk Lulusan SMA - Maria Teresa Novarina; sarjono Sarjono; Rina Nur Fitri (MAVIS : Jurnal Desain Komunikasi Visual, 2021)
Borderline Personality Disorder is a pattern of an unstable interpersonal relationship, self-image, emotion and impulsivity that started in early adulthood and shown by diverse contexts, the patient will experience denial interpersonal disturbance, impulsive behaviour and unstable mood which can put others or themselves in dangerous situation that can lead to suicidal behaviour. Borderline Personality Disorder can be diagnosed by some criteria of diagnosis but Indonesian people lack of knowledge in the importance of mental health can make the patients have some difficulty on getting the right treatment which can be seen on some cases where the mental disorder patients got shackled by their own families. A media that can show the occurrence and the symptoms can help public to understand what’s really happening to the patients of borderline personality disorder, that’s why manga comic can be the right media to give the information of the meaning, causes, symptoms, and how to handle it because the illustration can show the details of what the borderline personality disorder’s patients are really felt. Data collecting technique using interview and literature study, Borderline personality disorder comic designed in digital and have the main support media which is comic book in manga style on A5 paper size with 85 pages in total, 5 chapters in total, 15 pages per-chapter, coloured cover and chapter breaker, and black and white monochromatic main content.